Executive university managers’ experiences of strike and protest activity: A qualitative case study of a South African university - Dominguez-Whitehead, Y (South African Journal of Higher Education, 2011)
Strike and protest activity at South African universities continues to be prevalent nearly two decades after the dismantling of apartheid, although there has been a shift away from directing strikes and protests against the government (during the apartheid era), to directing them against higher education institutions and management (since the advent of democracy in 1994). Students, academics, and support staff continue to be dissatisfied with certain aspects of higher education, and university management must address ensuing strikes and protests. This article, based on qualitative case study research conducted at a South African university, examines the reported experiences of university executive management team members with respect to strike and protest activity. These reported experiences are analysed in the context of rising expectations that came about with recent higher education policy developments, newly institutionalised managerialism, and broader socio-economic implications.